Infectious Agents as Potential Drivers of α‐Synucleinopathies. Issue 3 (18th January 2022) - Linard, Morgane; Ravier, Alix; Mougué, Louisa; Grgurina, Iris; Boutillier, Anne‐Laurence; Foubert‐Samier, Alexandra; Blanc, Frédéric; Helmer, Catherine
Abstract: α‐synucleinopathies, encompassing Parkinson's disease, dementia with Lewy bodies, and multiple system atrophy, are devastating neurodegenerative diseases for which available therapeutic options are scarce, mostly because of our limited understanding of their pathophysiology. Although these pathologies are attributed to an intracellular accumulation of the α‐synuclein protein in the nervous system with subsequent neuronal loss, the trigger(s) of this accumulation is/are not clearly identified. Among the existing hypotheses, interest in the hypothesis advocating the involvement of infectious agents in the onset of these diseases is renewed. In this article, we aimed to review the ongoing relevant factors favoring and opposing this hypothesis, focusing on (1) the potential antimicrobial role of α‐synuclein, (2) potential entry points of pathogens in regard to early symptoms of diverse α‐synucleinopathies, (3) pre‐existing literature reviews assessing potential associations between infectious agents and Parkinson's disease, (4) original studies assessing these associations for dementia with Lewy bodies and multiple system atrophy (identified through a systematic literature review), and finally (5) potential susceptibility factors modulating the effects of infectious agents on the nervous system. © 2022 International Parkinson and Movement Disorder Society Abstract : α‐synuclein, a potential antimicrobial peptide, may accumulate in the periphery because of infectious agents present in the olfactory, gastrointestinal, or urogenital tracts. Its secondary spread through neuronal networks, in concomitance with genetic or environmental susceptibility factors, may damage the central nervous system.